Twitter formation of like-minded and dissimilar political communities during the 2015 mayoral campaign in Manizales (2019)
In the field of political communication, social networks have become an indispensable tool for election campaigns in recent years. In addition to opening communication and dialogue channels that are not available in other media and public spaces, these platforms promote the emergence of online communities that spawn conversations and exchange of political opinions. However, democratic participation in the digital age can lead to overcome certain obstacles, but also to deepen them. A content analysis technique to the messages published during the last twenty-five days of the 2015 mayoral campaign in the official Twitter accounts of the four candidates for Manizales Mayor’s Office, aimed at establishing if the followers of these accounts confronted their points of view with dissimilar perspectives, or if they expressed them only to users who were politically sympathetic to them. The results show a pivotal difference between the two accounts with the greatest participation of citizens regarding the formation of political communities: only one of facilitates the meeting between politically opposed voices, but they appeal to grievance, hostility and disqualification of the other as someone who has an opinion. Nevertheless, the dynamics of both accounts raise the same consequence: The fragmentation of the public sphere, the polarization and the dissolution of the essence of deliberative democracy.